Efektivitas Video Tutorial dalam Meningkatkan Ketrampilan Pemangkasan Rambut pada Mahasiswa Kecantikan - Anik Maghfiroh; Ifa Nurhayati; Florencia Angelina Bivan; Zahra Hafizshah; Eva Liantira Dinasa (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Hair cutting is an essential skill in beauty education that requires understanding of techniques and repeated practice. This research aims to determine the effectiveness of video tutorials in improving hair cutting skills among beauty students. The method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. Data analysis uses the Miles and Huberman model, as well as source triangulation to ensure data validity. The results showed that video tutorials can help students understand techniques visually and systematically, as well as improve their psychomotor skills. Students also showed a positive response to the use of videos because they can be accessed flexibly and facilitate independent learning. In conclusion, video tutorials are effective as a practical learning medium and are worthy of being integrated into the beauty education curriculum to improve the quality of skills learning.